Implementation of the REAP Strategy in the Aqidah Akhlak Course to Improve Student Literacy Ability - Dzulfikar Akbar Romadlon; Doni Septi; Budi Haryanto (Edukasi Islami : Jurnal Pendidikan Islam, 2020)
Aqidah Akhlak is a course that must be attended by PAI students because they will become teachers who will teach this course. The Aqidah Akhlak teacher requires the ability of "information literacy" in the themes that are taught. In this study, the writer will implement the REAP strategy in The Aqidah Akhlak subject to improve the information literacy ability of college students. This research is a Classroom Action Research (CAR) and the subject of research is a PAI UMSIDA student. This research was conducted in several stages, namely planning, action, observation, and reflection. Data collection is done by observation, field notes, interviews, tests, and documentation. After conducting classroom action research on the Aqidah Akhlak course, the results obtained in the Pre-Assessment averaged 50.5, then increased in the Post-Assessment an average of 86.7. Improvement in each cycle is followed by an increase in students' ability to browse the literature appropriately and use it in argumentation, increased activity in discussions, and increased task completion. Based on these results it can be concluded that the implementation of REAP strategy can improve students' information literacy abilities.